Residential Design for Future: Comparative Study on Benefits, Needs, and Characteristics of “Multi-Purpose Residential Architecture” Design Concept - Ting-Yueh Chen; Shu-Ying Tsai (Engineering Proceedings)
As the population ages, the living environment for the elderly is receiving more attention. “Multi-Purpose Residential Architecture” is transforming the traditional ways of building horizontally to meet a person’s daily activity and living needs. We surveyed 140 seniors over the age of 55 years to find their perspectives on building and expanding space vertically. Differences between the needs and expectations for living spaces between different ages of seniors were found. There are not enough facilities and space in Taiwan to meet the seniors’ needs for their daily lives, social activities, care, and other support.